The Influence of Managerial Ability, CFO Tenure, and Executive Compensation on Accounting Conservatism: The Moderating Role of Litigation Risk - Almi Hafiz; Erwin Saraswati; Arum Prastiwi (PT. Global Research Collaboration, 2026)
This study examines the influence of managerial ability, CFO tenure, and executive compensation on accounting conservatism, as well as the moderating role of litigation risk in manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2020–2024. This study employs panel data regression with interaction-based moderation analysis using a purposive sample of manufacturing firms. The model evaluates both the direct effects of internal managerial characteristics and the moderating role of external governance pressure proxied by litigation risk. The results show that managerial ability positively and significantly affects accounting conservatism, indicating that more competent managers tend to adopt prudent reporting practices. In contrast, CFO tenure has a negative and significant effect, suggesting that longer-serving CFOs may engage in less conservative reporting due to increased influence and familiarity with internal processes. Executive compensation exhibits a negative but insignificant effect. Furthermore, litigation risk does not moderate the relationships between managerial ability and CFO tenure with accounting conservatism; however, it significantly strengthens the relationship between executive compensation and accounting conservatism. This study is limited to manufacturing firms in Indonesia, which may restrict the generalizability of the findings across different industries and institutional settings. This study contributes to the literature by simultaneously integrating managerial ability, CFO tenure, and litigation risk within a single empirical framework of accounting conservatism in an emerging market context. Unlike prior studies that examine these factors separately, this research provides new insight into how internal managerial characteristics interact differently with external legal pressures in shaping conservative financial reporting behavior.